“Singing to the Choir:” The Struggle for Systemic Organizational Change in Community College Teaching - John M. Dirkx; Frank Conner (Adult Education Research Conference, 2006)
This study reports the results of a case study of a systemic change process in a community college aimed at fostering improvement of teaching practices. The results suggest that systemic change is limited by an organizational culture that is multiplistic and fragmentary.
Keywords: Professional development; systemic change; teaching improvement